MOBILE VOTING TOOLS FOR CREATING A NEW DESIGN OF INTERACTIVE LECTURE - Svetlana V. Titova; Tord Talmo (Высшее образование в России)
The objective of this paper is to investigate the pedagogical impact of mobile voting tools on creating collaborative environment at university lecture courses and getting immediate feedback from large classes. Our research demonstrated that integration of mobile voting app Student Response System (SRS) created in Norwegian University HiST (Trondheim) influenced not only lecture design - time management, the mode of material presentation, activity switch patterns - but also learners8teacher interaction, student collaboration and output, formats of activities and tasks. SRS supported lectures help instructors gradually get the grasp of a new type of digital classroom - flipped classroom, and then, in the long run, MOOC lecturing. The analysis based on qualitative and quantitative data collected from 56 undergraduate students showed that SRS supported lectures enhance their motivation, improve their intercultural competence and language skills.